Identification of the Quality of Ready-to-Eat Food Production Waste Water Using the MCDM Approach: Identifikasi Kualitas Air Sisa Produksi Makanan Siap Saji Dengan Menggunakan Pendekatan MCDM - Indah Apriliana Sari Wulandari; Nur Ravita Hanum; Fitria Trisna Sisiliani (Universitas Muhammadiyah Sidoarjo, 2023)
The rapid growth of Micro, Small, and Medium Enterprises (MSMEs) in the fast-food industry has raised concerns about the environmental impact, particularly regarding waste generation and its potential to pollute water sources. This research conducted in the Sidoarjo area aimed to identify the influence of MSME fast-food waste on water quality parameters, including Temperature, Turbidity, TDS, TSS, pH, DO, COD, Nitrate, Heavy Metal Cd, Total Coliform, and E-Coli. The study employed the Analytic Network Process (ANP) method, aided by Super Decision software version 2.10, to rank the most influential water quality criteria and prioritize alternative strategies to mitigate environmental issues. The results highlight crucial water quality parameters affected by MSME fast-food waste and present actionable insights for minimizing environmental impacts and safeguarding human health and the ecosystem. Highlights: Significant Environmental Impact: The rapid growth of Micro, Small, and Medium Enterprises (MSMEs) in the fast-food industry poses a significant environmental impact due to the waste generated during the production process. Water Quality Parameters: The study focuses on analyzing various water quality parameters affected by MSME fast-food waste, including Temperature, Turbidity, TDS, TSS, pH, DO, COD, Nitrate, Heavy Metal Cd, Total Coliform, and E-Coli. ANP Method for Mitigation: To address the environmental challenges posed by fast-food MSME waste, the research employs the Analytic Network Process (ANP) method, supported by Super Decision software version 2.10, to prioritize effective and sustainable alternatives for minimizing environmental pollution. Keywords: MSME, fast-food waste, water quality, environmental issues, ANP method